Twenty Years After the Iowa Gambling Task: Rationality, Emotion, and Decision-Making - Jong-Tsun Huang (Frontiers Research Topics, 2018)
The world is full of uncertainty. In unpredictable circumstances, can emotions facilitate advantageous decision-making? A neuroscience team, led by Antonio Damasio, explored this question using the Iowa Gambling Task (IGT). To the present day, the findings of numerous IGT-related investigations strongly influence clinical and interdisciplinary research, for example, in neuroeconomics and neuromarketing. This special issue examines IGT-based research progress over the past 20 years through literature reviews, clinical examinations, model construction, theoretical integration, and brain imaging technology. Both supportive and opposing viewpoints are provided to frame correlations between rationality, emotion, decision-making, and IGT. Potential future directions for IGT studies are discussed